Toksisitas Ekstrak Etanol dan Ekstrak Air dari Daun Jotang Kuda (Synedrella nodiflora (L.) Gaertn.), Daun Gandarusa (Justicia Gendarussa Burm.F.), dan Daun Pulutan (Urena lobata L.) dengan Brine Shrimp Lethality Test: Toxicity of Ethanol Extract and Water Extract of Synedrella nodiflora(L.) Gaertn. Leaves, Justicia gendarussa Burm.f. Leaves, and Urena lobata L. Leaves with Brine Shrimp Lethality Test - Widodo, Agustinus; Khumaidi, Akhmad; A. Lasongke, Putri Faradila (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Jotang kuda (Synedrella nodiflora (L.) Gaertn.), gandarusa (Justicia gendarussa Burm.f.) and pulutan (Urena lobata L.) leaves are used by several tribes in Central Sulawesi for the treatment of cancer. This study aims to determine the value of LC50 (Lethal Concentration 50) of ethanol and water extracts from the S. nodiflora, J. gendarussa and U. lobata leaves and identify the class of chemical compounds contained in extracts with the highest toxicity. The ethanol extract was obtained by the maceration method using ethanol 96% and the water extract was obtained by the infusionmethod. The extract toxicity test was carried out byBrine Shrimp Lethality Test (BSLT) and dentification test was carried out by Thin Layer Chromatography (TLC). The toxicity test results (LC50) of 96% ethanol extract and water extract of S. nodiflora leaves were 395.60 Î¼g/ml and 109.25 Î¼g/ml; J. gendarussa leaves 713.34 Î¼g/ml and 18.02 Î¼g/ml; and U.lobata leaves 188.38 Î¼g/ml and 85.37 Î¼g/ml, respectively. The results of identification showed that the water extract of the J. gendarussa leaves containing alkaloids, flavonoids, phenolics, saponins, and steroids-terpenoids. The results of this study indicated that the extracts of S. nodiflora leaves, J. gendarussa leaves, and U. lobata leaves are potential to be developed as anticancer.